Learning Transformation at MTSN 3 Deli Serdang Through Digital Models: 21st Century Educational Innovation - Dongoran, Faisal Rahman; Amiruddin, Amiruddin; Khairany, Indah (Journal Of Education And Teaching Learning (JETL), 2024)
This article explores significant changes in the teaching methods at Madrasah Tsanawiyah Negeri 3 Deli Serdang through the implementation of a digital-based learning model as an innovative step in 21st-century education. The primary objective of this research is to analyze the positive impact of the digital model on the learning process and academic achievements of students. With a focus on enhancing student engagement, accessibility to learning resources, and fostering creativity, teachers at MTsN 3 Deli Serdang utilize technology to deliver interactive and engaging learning materials. The research findings indicate a substantial improvement in student participation, learning quality, and academic performance, providing compelling evidence of the effectiveness of implementing digital- based learning models in this educational institution. Despite facing some technical challenges and the need for teacher training, this transformation paves the way for a more inclusive education system that aligns with the evolving demands of the times.